2013
DOI: 10.1093/abbs/gmt109
|View full text |Cite
|
Sign up to set email alerts
|

MiRNA-218, a new regulator of HMGB1, suppresses cell migration and invasion in non-small cell lung cancer

Abstract: MicroRNAs (miRNAs) function as negative regulators of gene expression involved in cancer metastasis. The aim of this study is to investigate the potential roles of miR-218 in non-small cell lung cancer and validate its regulation mechanism. Functional studies showed that miR-218 overexpression inhibited cell migration and invasion, but had no effect on cell viability. Enhanced green fluorescent protein reporter assay, real-time polymerase chain reaction and western blot analysis confirmed that miR-218 suppress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 32 publications
1
55
0
Order By: Relevance
“…It is well known that one miRNA may target many genes in different cell systems and miR-218 is no exception. There are several relatively common target genes of miR-218 in cancers such as BMI-1 [14, 27, 28], surviving [29-32] and HMGB1 [26, 33-36]. BMI-1 is a member of the polycomb group (PcG) of genes and is the first identified PcG transcriptional repressor.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that one miRNA may target many genes in different cell systems and miR-218 is no exception. There are several relatively common target genes of miR-218 in cancers such as BMI-1 [14, 27, 28], surviving [29-32] and HMGB1 [26, 33-36]. BMI-1 is a member of the polycomb group (PcG) of genes and is the first identified PcG transcriptional repressor.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that miR-218 expression is downregulated in many tumors including ESCC (15)(16)(17)(18)(19)(20) and is involved in cancer initiation and development (15)(16)(17)(18)(19)(20)(21)(22) SOT (38), Rob1 receptor (39) as well as LAmb3 (40), which are involved in several different signaling pathways, suggesting that miR-218 is a tumor suppressor miRNA and plays a crucial role in the initiation, development and metastasis of tumors. Therefore, we reasonably speculated that miR-218 suppresses the tumor growth of ESCC in vitro and in vivo by regulating multiple target genes.…”
Section: Discussionmentioning
confidence: 99%
“…microRNA-218 (miR-218) is a recently discovered miRNA and is downregulated in several types of cancer, such as gastric cancer (15,16), cervical squamous cell carcinoma (17), medulloblastoma (18), lung cancer (19) and glioblastoma (20). Accumulating evidence demonstrates that miR-218 acts as a tumor suppressor and confers an inhibitory effect on cancer cell proliferation, migration and invasion by targeting genes (15)(16)(17)(18)(19)(20)(21)(22). In particular, recently studies have demonstrated that overexpression of miR-218 increased chemosensitivity to cisplatin (CDDP) in cervical cancer cells (23).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, microRNA-325-3p [21] and MiRNA-218 [22], as the new regulators of HMGB1, regulated cell invasion and proliferation by targeting HMGB1 in non-small cell lung cancer. Zhang et al [23] found that HMGB1 and NF-kappaB p65 protein expression showed a positive correlation, and HMGB1 and NF-kappaB p65 expression might be related to non-small cell lung cancer metastasis.…”
Section: Introductionmentioning
confidence: 99%